2020
DOI: 10.1039/d0nj02992k
|View full text |Cite
|
Sign up to set email alerts
|

Can nitrous acid contribute to atmospheric new particle formation from nitric acid and water?

Abstract: The structural and thermodynamic properties of the (HNO3)(HONO)(H2O)n (n=1-6) clusters are investigated by density functional theory on the M06-2X/6-311+G(2d,p) level. Atoms in molecules (AIM) analysis and Natural Bond Orbital (NBO)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 81 publications
1
5
0
Order By: Relevance
“…It can be seen that the Δ G values of nitric acid monohydrate, dihydrate, and trihydrate are negative as −0.78, −0.83, and −0.92 kcal mol –1 , respectively, indicating that the forming processes for NA-W n ( n = 1–3) are spontaneous in the atmosphere, while tetrahydrate, pentahydrate, and hexahydrate are not formed spontaneously from the positive Δ G . This is consistent with previous research . Observing those Δ G values of NA-amide-W n ( n = 1–6) clusters, it is found that most of them are negative, suggesting that these clusters can spontaneously form in the atmosphere.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It can be seen that the Δ G values of nitric acid monohydrate, dihydrate, and trihydrate are negative as −0.78, −0.83, and −0.92 kcal mol –1 , respectively, indicating that the forming processes for NA-W n ( n = 1–3) are spontaneous in the atmosphere, while tetrahydrate, pentahydrate, and hexahydrate are not formed spontaneously from the positive Δ G . This is consistent with previous research . Observing those Δ G values of NA-amide-W n ( n = 1–6) clusters, it is found that most of them are negative, suggesting that these clusters can spontaneously form in the atmosphere.…”
Section: Resultssupporting
confidence: 92%
“…This is consistent with previous research. 74 Observing those ΔG values of NA-amide-W n (n = 1−6) clusters, it is found that most of them are negative, suggesting that these clusters can spontaneously form in the atmosphere. In other words, they are atmospheric-related.…”
Section: Clusters Of Hno 3 -Amide-w N (N = 1−6) 321 Structures Thermo...mentioning
confidence: 99%
“…The distance d (O–O) between two oxygen atoms in the hydrogen bonds can be used as an indicator of the bond strength; combined with the AIM data of some clusters presented in Table S7, it is concluded that for homo-nuclear hydrogen bonds, d (O–O) < 2.65 Å indicates strong hydrogen bonds, at which point ρ( r ) > 0.048 au. For hetero-nuclear hydrogen bonds, ρ( r ) = 0.037 au is taken as the critical point to distinguish strong and medium-strength hydrogen bonds, which has been mentioned in a previous study …”
Section: Resultsmentioning
confidence: 99%
“…The distribution of Glu-U-5W-a/c also declines in Figure e, but its changing tendency is not as obvious as Glu-U-3W-b. Studies have proved that the Δ G ° of clusters increases with the increase of temperature; the values increase by various magnitudes because of the different entropies (Δ S °) of structures containing diverse numbers of hydrogen bonds. , In view of the different phenomena in Glu-U-3W clusters, the Δ S ° at T = 298.15 K, with ΔΔ G ranging from 220 to 320 K, and the number of hydrogen bonds in Glu-U-3W, Glu-U-3W-a/b/c were calculated, and the data are listed in Table S14. In the above four structures, the Δ S ° values are −570.28, −570.00, −614.93, and −585.12 J mol –1 K –1 ; the ΔΔ G values are 13.65, 13.65, 14.69, and 13.99 kcal mol –1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation